2008
DOI: 10.1002/jbm.a.31875
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the osteoinductive capacity and angiogenicity of an in vitro generated extracellular matrix

Abstract: In this study, the osteoinductive potential of an in vitro generated extracellular matrix (ECM) deposited by marrow stromal cells seeded onto titanium fiber mesh scaffolds and cultured in a flow perfusion bioreactor was investigated. Culture periods of 8, 12, and 16 days were selected to allow for different amounts of ECM deposition by the cells as well as ECM with varying degrees of maturity (Ti/ECM/d8, Ti/ECM/d12, and Ti/ECM/d16, respectively). These ECM-containing constructs were implanted intramuscularly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 30 publications
2
44
0
Order By: Relevance
“…The previous study reports have indicated that in vitro-generated ECM had an impact on the osteoblastic differentiation of mesenchymal stem cells in vitro, and in vivo. 9,10,19,20 In the present study it has been hypothesized that HA modified by the ECM secreted by the primary cells possesses necessary stimuli to enhance bone tissue repair, and provides a three-dimensional environment for the host progenitor The basic approach used in this study was to allow cells to deposit their own ECM followed by removal of the cells while preserving the native constituents and topography of the generated matrix. The primary cells required culture at high density with the media supplemented with high l-AA concentration to produce 3D ECM matrices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The previous study reports have indicated that in vitro-generated ECM had an impact on the osteoblastic differentiation of mesenchymal stem cells in vitro, and in vivo. 9,10,19,20 In the present study it has been hypothesized that HA modified by the ECM secreted by the primary cells possesses necessary stimuli to enhance bone tissue repair, and provides a three-dimensional environment for the host progenitor The basic approach used in this study was to allow cells to deposit their own ECM followed by removal of the cells while preserving the native constituents and topography of the generated matrix. The primary cells required culture at high density with the media supplemented with high l-AA concentration to produce 3D ECM matrices.…”
Section: Discussionmentioning
confidence: 99%
“…10 Briefly, at the end of the culture period all constructs were rinsed in DPBS, and either frozen in LN 2 for 10 min, undergoing freeze-thaw cycle three …”
Section: Scaffolds Decellularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such eECM were also demonstrated to support the in vitro expansion of late-passaged human MSC, and also to dramatically improve their osteogenic capacity [72,73]. In vivo, eECM displayed efficient engraftment [74] and vascularization [75] and was capable to undergo remodeling onto an immature osteoid tissue [71]. eECM was successfully shown to act as functional/instructive template for the regulation and/or recruitment of osteoprogenitor cells, although it could not ectopically induce frank bone formation in mouse and rat models [71,76].…”
Section: Decellularized Engineered Ecm (Eecm)mentioning
confidence: 92%
“…Recently, investigations have focused on designing new vehicles by using the decellularized matrices (natural ECM). Numerous studies have shown the promising osteogenic effects of MSC-laden decellularized ECMs in the absence of osteogenic cell culture supplements or any growth factors [Datta et al, 2006;Pham et al, 2009;Liao et al, 2010]. One study showed that MSCs seeded with ECM construct and cultured in medium either with or without dexamethasone revealed similar amounts of calcium deposition after 16 days.…”
Section: Delivery Of Cells Within a 3d Dynamic Environmentmentioning
confidence: 99%